Respuestas

2012-07-17T02:09:16+02:00

                                                                   

                                        5(x-2)=3(x-1)+1

                                           solucion:

                                         5x-10=3x-3+1

                                         5x-3x=10-3+1

                                              2x=8

                                              x=8/2

                                              x=4

  • Usuario de Brainly
2012-07-17T02:10:03+02:00

 5(x-2)=3(x-1)+1

5X - 10 = 3X - 3 + 1

5X - 3X = -3 + 1 + 10

2X = 8

X = 8/2

X = 4


Saludos,

jvilchez